THE EFFECTIVENESS OF THE GAME APPROACH ON BASIC MOVEMENT SKILLS OF ELEMENTARY SCHOOL STUDENTS - Ahmad Safudin (Universitas Syiah Kuala, 2022)
The purpose of the study was to test the effectiveness of the basic movement learning model. The model combines the basic movement learning and games to support basic movement skill for elementary school students. Fundamental movement is very important role in the achievement of the goal basic movement learning. Therefore the goal in basic movement learning is with very effective basic motion. Therefore a good basic motion is needed by elementary school students.Materials and methods The research approach used is quantitative. This type of research is experiment with randomized control group pre-test post-test design. The population of this study is all elementary school students in Palembang of amounted to 120 students as with 60 experimental group students and 60 students as a control group. The instrument used to collect data is a test of basic movement skill. Data analysis technique using t-test. The result of this research showed that product of basic movement learning is appropriate for students in grade 2. It was confirmed by basic movement skill test that elucidate that the basic movement learning model can be carried well. Other than that the basic movement learning is effectively used by the second grader of elementary school students in increasing their basic movement skill. t-count value of 27.384 t-table 2.00 Conclusions which means that basic movement learning model is effective against improving the basic movement skill for elementary school students.